PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING DAN MOTIVASI TERHADAP HASIL BELAJAR FIQH SISWA MADRASAH TSANAWIYAH NEGERI STABAT - Siti Rusmayani (EDU-RILIGIA: Jurnal Ilmu Pendidikan Islam dan Keagamaan, 2017)
Abstrack: The purpose of this study is to (1) to know the difference of learning result of Fiqh studentstaught by using problem based learning and using KTSP. 2) know the difference of learning result Fiqhstudents who have high motivation with low motivated students. (3) to know the interaction betweenproblem based learning model and motivation toward student learning result in Fiqh subject. The locationof this research was conducted at MTsN Negeri Stabat Langkat. This research uses quantitativeapproach in the form of experiment.Result of research based on result of data analysis which have beendone that is Varian Analysis and Tuckey Test hence found significant difference between result of studentlearning taught by Problem Based Learning learning with KTSP learning model that group of studenttaught by using problem based learning model get result of learning Higher than students taught usingKTSP learning on fiqh materials in Madarash Tsnawiyah Negeri Stabat. There is an interaction betweenthe learning model and the students’ learning motivation on the learning outcomes in fiqh material inMadarasah Tsanawiyah Negeri Stabat.